FUNGSI KEPEMIMPINAN DALAM PROSES PENEMPATAN KERJA KARYAWAN - Emiyati Emiyati (JEM Jurnal Ekonomi dan Manajemen, 2021)
This study aims to analyze the function of leadership in the process of employee job placement by taking the locus of study on CV. Angel certainly needs various instruments, ranging from facilities and infrastructure to human resources, as well as the character of a leader. The character of a leader and the function of a leader itself is one of the main factors in the management of an organization, both government and private. This study uses a qualitative descriptive method, the researcher collects data obtained from the sources studied through observation, interviews, and documentation related to the research title. The results showed that employees at CV. Angel can describe the policies given by the leadership in the form of a positive response to the tasks and responsibilities assigned to them.